Competency-Based Pay And Service Quality: An Empirical Study Of Malaysian Public Organisations - Azmi, Ilhaamie Abdul Ghani; Ahmad, Zainal Ariffin; Zainuddin, Yuserrie (Asian Academy of Management (AAM), 2009)
A higher number of complaints have been filed by the public due to delays by public sectors in taking action and providing services to the public. This suggests that service quality is not being delivered as expected by customers. With competency-based pay being offered in the public sector under the System Saraan Malaysia (SSM), which aims to produce capable workers who are responsive to customers' demands by providing quality services, one would expect that there would be an improvement in the general quality of the services rendered. Thus, this research aimed to investigate the relationship between the extent of competency-based pay practices and service quality. The findings suggest that there is a positive relationship between competency-based pay practices and service provision, one of the SERVQUAL dimensions found in this study. Thus, Malaysian public organisations should offer this type of pay as frequently as possible in order to motivate civil servants to provide quality services to the public.